1990
DOI: 10.1029/jd095id05p05533
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of the fine‐scale structure and turbulence in the mesosphere and lower thermosphere by means of electrostatic positive ion probes

Abstract: The paper presents and discusses a large set of in situ measurements of fine‐scale structure in the mesosphere and lower thermosphere at high latitudes. The experimental technique used is a rocket‐borne electrostatic positive ion probe with linear amplification and high precision and time resolution. This type of probe has proved to be very efficient. The accuracy and limitations of the experiment are discussed. The measured ion density fluctuations are used as passive tracers for motions in the nonionized air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 30 publications
2
66
0
Order By: Relevance
“…2 we show the observed currents I G1 , I G2 and I BP to grids G1, G2, and to the bottom plate and I CONE to the CONE electron probe (Blix et al, 1990). In Fig.…”
Section: A New Look At the Ect-0measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 we show the observed currents I G1 , I G2 and I BP to grids G1, G2, and to the bottom plate and I CONE to the CONE electron probe (Blix et al, 1990). In Fig.…”
Section: A New Look At the Ect-0measurementsmentioning
confidence: 99%
“…However, secondary production by the dust impact on the bottom plate at low impact angles θ i Ann. Geophys., 25, 623-637, 2007 www the CONE electron probe (Blix et al, 1990). In Fig.…”
Section: A New Look At the Ect-0measurementsmentioning
confidence: 99%
“…Ionospheric plasma densities were measured by a set of different probes, yielding relative densities of electrons (Langmuir probe and CONE), positive ions (by positive ion probe), and charged aerosols (by particle detector, PD), including their variations down to meter scales (e.g., Blix et al, 1990a). Absolute electron densities were precisely measured with the radio-wave propagation technique (Bennett et al, 1972;Jacobsen and Friedrich, 1979).…”
Section: Wadis Payloadmentioning
confidence: 99%
“…Hinze, 1975) will increase. The time scales modelled here correspond to the Kolmogorov microscale η (Kolmogorov, 1941), at which, one could roughly say that turbulent eddies are allowed to complete, since inertia overcomes viscous drag (although this visualisation is perhaps better suited to the inner scale = 7.4η; Blix et al, 1990) At longer time scales, and, therefore, at scales within the inertial subrange (Obukov, 1941), the ionisation structure within the trail is quickly destroyed; however, after this time delay, the backscattered power has become so weak that it does not feature in the determination of the characteristic fading time. It should also be stressed that the turbulent contribution to the dissipation of the ionisation structure is indeed just that: a contribution, an enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The length scale η is the scale at which the extrapolations of the slopes of viscous and inertial regimes of the turbulent spectrum meet. An alternative is to consider the length scale at which the inertial subrange begins to depart from a power-law dependence; this scale, the inner scale l 0 , is typically given by 7.4η (Blix et al, 1990), this perhaps better representing the smallest eddies, and is also shown in Fig. 3.…”
Section: Simulation Of Ambipolar Diffusivity Profilesmentioning
confidence: 99%